2022
DOI: 10.1097/md.0000000000028500
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis-related autophagy genes in female lung adenocarcinoma

Abstract: To screen the prognosis-related autophagy genes of female lung adenocarcinoma by the transcriptome data and clinical data from The Cancer Genome Atlas (TCGA) database. In this study, screen meaningful female lung adenocarcinoma differential genes in TCGA, use univariate Cox proportional regression model to select genes related to prognosis, and establish the best risk model. In this study, Gene Ontology and Kyoto Encyclopedia of Genes and Genomes were applied for carrying out bioinformatics analysis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…ITGA6, a member of the integrin family, plays a key role in the interaction between several cell types and participates in multiple biological processes, including cell proliferation and invasion [34]. Among the ATGs in female lung adenocarcinoma, there was a significant relationship between ITGA6 and its survival prognosis [35]. The present study showed that the autophagy-related gene, ITGA6, significantly increased in the progression of CAS.…”
Section: Discussionmentioning
confidence: 47%
“…ITGA6, a member of the integrin family, plays a key role in the interaction between several cell types and participates in multiple biological processes, including cell proliferation and invasion [34]. Among the ATGs in female lung adenocarcinoma, there was a significant relationship between ITGA6 and its survival prognosis [35]. The present study showed that the autophagy-related gene, ITGA6, significantly increased in the progression of CAS.…”
Section: Discussionmentioning
confidence: 47%
“…PTK6, also known as Protein Tyrosine Kinase 6, is another gene of interest that has been implicated in cancer pathogenesis [19][20][21]. Previous investigations have demonstrated the correlation between PTK6 expression and cancer stages in ovarian carcinoma, suggesting its potential as a staging biomarker for disease prognosis and management [22,23]. SERPINA1, or Serpin Family A Member 1, has been extensively studied in various cancers and is known to play a crucial role in regulating tumor growth and metastasis [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that upregulation of the Bak1 protein expression level enhances the proliferation and migration of various tumour cells, including lung cancer cells[18], melanoma cells [19] and cervical cancer cells [20]. In addition, increased Bak1 protein expression is closely associated with poor prognosis of patients with non-small cell lung cancer [21]. Bak1 is expressed in tumour cells in a tissue-and time-speci c manner.…”
Section: Introductionmentioning
confidence: 99%